Entropic rectification and current inversion in a pulsating channel - Carusela, María Florencia (2017)
We show the existence of a resonant behavior of the current of Brownian particles confined in a pulsating channel. The interplay between the periodic oscillations of the shape of the channel and a force applied along its axis leads to an increase of the particle current as a function of the diffusion coefficient. A regime of current inversion is also observed for particular values of the oscillation frequency and the applied force. The model proposed is based on the Fick-Jacobs equation in which the entropic barrier and the effective diffusion coefficient depend on time. The phenomenon observed could be used to optimize transport in microfluidic devices or biological channels.